The Use of Quetiapine for Comorbid Bipolar and Obsessive Compulsive Disorders - Yoldi-Negrete, María; Flores-Ramos, Mónica; Rodríguez-Ramírez, Alejandra Montserrat; Armando, Carvajal-Lohr; æ#129;vila-Solorio, Jorge; María Alejandra, Martin-Manzo; Alejandra, Andrade; González-Flores, Leonardo (Current Psychopharmacology, 2015)
Background: Both Bipolar Disorder (BD) and Obsessive Compulsive Disorder (OCD) are chronic psychiatric conditions, the first characterized by depressive and manic mood episodes and the latter characterized by obsessions and compulsions. The comorbidity between BD and OCD is not rare, and the presence of both conditions conveys important complications. The treatment supposes a challenge since antidepressants, first choice of treatment for OCD, carry an important risk for bipolar patients. Objective: In the present review our aim was to find evidence on Quetiapine's efficacy in the treatment of bipolar disorder with comorbid OCD. Method: We performed a literature review on the treatment options for comorbid BD and OCD, Quetiapine’s use in OCD and anxiety disorders and finally a MEDLINE search about the use of Quetiapine for this specific indication. Conclusion: The use of Quetiapine could be justified in patients with cycling OCD and in those who have shown benefit from this antipsychotic for BD and can tolerate adjunctive antidepressants. Still, clinical trials including this specific comorbid population should be performed to consider Quetiapine as part of BD-OCD patient’s treatment.
Keywords: SSRI